2013
DOI: 10.1002/zaac.201300133
|View full text |Cite
|
Sign up to set email alerts
|

Tetrakis(ferrocenecarbonitrile) Copper(I) Complexes

Abstract: The homoleptic tetrakis(ferrocenecarbonitrile) copper(I) complexes [Cu(N≡CFc)4]A [A = BF4 (3a), A = SO3CF3 (3b)] were succefully prepared by treatment of copper with the copper(II) salt [CuA2]·xH2O [A = BF4, x = 5 (1a); A = SO3CF3, x = 0 (1b)] in presence of cyanoferrocene (2). For 3a the tetrahedral arrangement of the four ferrocenecarbonitrile ligands at the copper atom was proven by single X‐ray diffraction studies. The FcC≡N units are weakly bonded to copper, which is reflected by a complete ligand exchang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 73 publications
1
8
0
Order By: Relevance
“…A synthesis for ferrocenecarbonitrile has already been described in 1957 (Graham et al, 1957); however, only one example of an application in electrochemical studies has been described by Dowling et al (1981). This prompted us to synthesize ferrocenecarbonitrile transition metal complexes to investigate the electronic properties of the -C N-M-N Cbridging units (Strehler et al 2013(Strehler et al , 2014. In a continuation of this work, we present herein the synthesis and crystal structure of the related ruthenocenecarbonitrile, (I).…”
Section: Chemical Contextmentioning
confidence: 99%
“…A synthesis for ferrocenecarbonitrile has already been described in 1957 (Graham et al, 1957); however, only one example of an application in electrochemical studies has been described by Dowling et al (1981). This prompted us to synthesize ferrocenecarbonitrile transition metal complexes to investigate the electronic properties of the -C N-M-N Cbridging units (Strehler et al 2013(Strehler et al , 2014. In a continuation of this work, we present herein the synthesis and crystal structure of the related ruthenocenecarbonitrile, (I).…”
Section: Chemical Contextmentioning
confidence: 99%
“…A three electrode cell, which utilized a Pt auxiliary electrode, a glassy carbon working electrode (surface area 0.031 cmò) and an Ag/Ag + (0.01 mol · L –1 AgNO 3 ) reference electrode was used as described in reference. [ 36,41–50 ] Successive experiments under the same experimental conditions showed that all formal potentials were reproducible within ±5 mV. Experimental potentials were referenced against an Ag/Ag + reference electrode, but results are presented referenced against ferrocene [FcH/FcH + couple = 220 mV vs. Ag/Ag + , Δ E p = 61 mV; FcH = Fe(η 5 ‐C 5 H 5 ) 2 ] as an internal standard.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, a weak electron transfer by generation of the mixedvalence species [Ru(N CFc)(NH 3 ) 5 ] 3+ [Fc = Fe( 5 -C 5 H 4 )( 5 -C 5 H 5 )] has been described (Dowling et al, 1981). We recently reported on the synthesis, characterization and electrochemical properties of platinum and copper complexes containing a -C N-M-N C-(M = Cu or Pt) bridging unit between two redox-active ferrocenyl moieties (Strehler et al, 2013(Strehler et al, , 2014 to achieve a direct comparison with the -C C-M-C C-building blocks. In addition, the coordination of ferrocene-1,1 0 -dicarbonitrile towards PtCl 2 resulted in an oligomeric complex (Strehler et al, 2014).…”
Section: Chemical Contextmentioning
confidence: 99%